2021
DOI: 10.1002/mds.28818
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Dopamine Transporter Imaging Trajectories in a Cohort of Parkinson's Disease Patients with GBA Mutations

Abstract: A BS TRACT: Background: Glucosylceramidase (GBA) mutations are considered the most common genetic risk factors for developing Parkinson's disease (PD). Objectives: We aimed to assess, at different time points, the integrity of brain striatal and extra-striatal dopamine pathways and clinical phenotype of a group of PD subjects bearing heterozygous GBA mutations (GBA-PD), compared with a group of idiopathic PD patients (iPD) stratified by age at disease onset. A longitudinal approach was adopted to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 54 publications
10
28
0
Order By: Relevance
“…These imaging findings were in line with clinical observations demonstrating a more rapid trajectory of motor and cognitive impairment in GBA‐PD compared to iPD 18 . Also a study conducted on the Parkinson's Progression Markers Initiative (PPMI) cohort reported significant GM differences in GBA‐PD compared with iPD patients 17 . In particular, both GBA‐PD and late‐onset (LO)‐iPD showed greater structural volume reductions compared with the early‐onset (EO)‐iPD group.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…These imaging findings were in line with clinical observations demonstrating a more rapid trajectory of motor and cognitive impairment in GBA‐PD compared to iPD 18 . Also a study conducted on the Parkinson's Progression Markers Initiative (PPMI) cohort reported significant GM differences in GBA‐PD compared with iPD patients 17 . In particular, both GBA‐PD and late‐onset (LO)‐iPD showed greater structural volume reductions compared with the early‐onset (EO)‐iPD group.…”
Section: Resultssupporting
confidence: 85%
“…The clinical follow‐up (up to 6 years) in this cohort showed greater worsening in motor, cognitive, and autonomic functions in GBA‐PD versus EO‐iPD and in LO‐iPD versus EO‐iPD but no differences between GBA‐iPD and LO‐iPD. LO‐iPD is associated with a more aggressive form of disease 51 : the findings of this study (see the Nigrostriatal Imaging section) support the hypothesis that GBA mutations participate to accelerate the neurodegenerative processes in PD 17 …”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Utilising fluorodopa PET and transcranial sonography, no significant difference in nigrostriatal imaging has been reported between iPD and GBA1 -PD patients (Kono et al 2007 ; Kraoua et al 2009 ; Goker-Alpan et al 2012 ; Barrett et al 2013 ; Lopez et al 2020 ). Longitudinal investigations using single-photon emission computerised tomography (SPECT) and structural MRI have revealed a more accelerated disease course in GBA1 -PD compared to iPD (Caminiti et al 2022 ; Leocadi et al 2022 ). Of note, iPD patients demonstrated similar patterns of cortical thinning to GBA1-PD 5 years post baseline MRI scans (Leocadi et al 2022 ).…”
Section: Features Of Gba1 -Associated Parkinson Di...mentioning
confidence: 99%